2012
DOI: 10.1242/jeb.065904
|View full text |Cite
|
Sign up to set email alerts
|

Spectral transmission of the principal-eye corneas of jumping spiders: implications for ultraviolet vision

Abstract: SUMMARYUltraviolet (UV) vision plays an important role in interspecific and intraspecific communication in many animals. However, UV vision and its adaptive significance have been investigated in only approximately 1% of more than 5000 species of jumping spiders (Araneae: Salticidae), renowned for their unique, complex eyes that support exceptional spatial acuity and visually based behaviour. To appreciate the adaptive significance of UV vision, it is important to establish whether salticids can perceive UV an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…the crab spider E. tricuspidata; Table 1), spiders inhabiting forest shade and burrows where there is a lower level of illumination or a shift in the ambient light spectrum to longer wavelengths tended to have corneas with a higher T 50 cutoff value than those living in open areas, where there are high levels of sunlight. This is consistent with the salticids that have already been examined (Hu et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…the crab spider E. tricuspidata; Table 1), spiders inhabiting forest shade and burrows where there is a lower level of illumination or a shift in the ambient light spectrum to longer wavelengths tended to have corneas with a higher T 50 cutoff value than those living in open areas, where there are high levels of sunlight. This is consistent with the salticids that have already been examined (Hu et al, 2012).…”
Section: Discussionsupporting
confidence: 90%
“…Our recent study has also shown that the spectral transmission of salticid corneas varies with light habitat (Hu et al, 2012): the corneas of salticids inhabiting open bush have a higher relative transmission at short wavelengths in the UV spectrum than do species living in the forest. Non-salticid spiders also live in a wide range of habitats that differ greatly in photic conditions.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations